The Benefits of Learning Media for Sunday School Students' Ability to Hear Bible Stories - Banni, Lidya Dyani; Yarmi, Gusti; Sarifah, Iva (BIA': Jurnal Teologi dan Pendidikan Kristen Kontekstual, 2025)
The lecture method, storytelling, and picture media are the most commonly used approaches and tools in Sunday school learning. They influence children's ability to focus and listen during Bible stories. This study aims to describe how various learning media can support the storytelling method to enhance children's listening skills in Bible stories, which Sunday school teachers can implement. The research uses library methods, examining various scientific studies from relevant sources. The data source consists of secondary data published previously, such as books, journals, and prior research. Data was collected through documentation, and the analysis used content analysis to draw reproducible conclusions. The study identified several media that can be used in the Sunday school Bible storytelling approach to improve children's listening skills, including (1) hand puppet media, (2) pictures, (3) audiovisual media, and (4) digital applications. In addition, role-playing can also be incorporated into Sunday school lessons to enhance children's listening skills in Bible stories.